2019
DOI: 10.4067/s0717-95022019000100232
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Analysis of Nasolabial Soft Tissues While Smiling Using stereophotogrammetry (3dMDTM)

Abstract: The nasolabial region is the central esthetic unit of the face and is considered one of the most important determinants of the facial esthetic. The facial morphometry of soft tissues is a very important tool in facial surgery. Advances have been made recently in the capture and analysis of 3D images, which offer great development potential in the diagnosis and treatment of facial deformities. The aim of this study was to characterize the nasolabial region of patient candidates for orthognathic surgery using 3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
0
6
0
2
Order By: Relevance
“…Despite the considerable quantity of image acquisition systems presently employed for 3D photography, research use for this type of imaging is limited to a handful of devices, of which 2 are the most extensively utilized. First, we found that the most used system was the 3dMD, 10,[12][13][14][15][16][17][18][19][20][21][22][23][24] which consists of 2 groups of 3 cameras, each located at 45 degrees to the right and left side target, and was used by 52% of the authors, followed by the Vectra M3, [25][26][27][28][29][30][31][32] which consists of a device composed of 3 groups of 2 cameras each and was used by 28% of the authors. In contrast, some other systems were used by some authors.…”
Section: System Usedmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the considerable quantity of image acquisition systems presently employed for 3D photography, research use for this type of imaging is limited to a handful of devices, of which 2 are the most extensively utilized. First, we found that the most used system was the 3dMD, 10,[12][13][14][15][16][17][18][19][20][21][22][23][24] which consists of 2 groups of 3 cameras, each located at 45 degrees to the right and left side target, and was used by 52% of the authors, followed by the Vectra M3, [25][26][27][28][29][30][31][32] which consists of a device composed of 3 groups of 2 cameras each and was used by 28% of the authors. In contrast, some other systems were used by some authors.…”
Section: System Usedmentioning
confidence: 99%
“…In contrast, most of the authors used chairs with high backs to improve back support, reducing variations due to mobility or changes in body posture. [12][13][14][15][16]18,19,25,[27][28][29][30][31][32][33]36,37,41 Head Posture Riml et al (2011) 42 showed the influence of head position on facial analysis, noting that different postures yield different results in measurements on facial photographs. In this study, most authors describe the positioning of the head for image acquisition as: "natural head position," (NHP) noting that this is a reproducible and proven position, described as "the head positioned in a relaxed manner while the person observes a fixed point on the horizon."…”
Section: Body Posturementioning
confidence: 99%
See 1 more Smart Citation
“…Embora, alcançar a precisão adequada seja difícil, a análise com essa tecnologia 3D pode gerar bons resultados além de permitir melhores abordagens (PARRA M et al,2019).…”
Section: Introductionunclassified
“…Dentre os métodos existentes, a estereofotogrametria ou foto 3D é um método não invasivo que permite uma reprodução tridimensional precisa das estruturas faciais. Embora, alcançar a precisão adequada seja difícil, a análise com essa tecnologia 3D pode gerar bons resultados além de permitir melhores abordagens (PARRA M et al, 2019).…”
Section: Introductionunclassified